ADVANTAGES OF LEARNING ENGLISH AS A SECOND LANGUAGE (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
English is considered a dominant language in many countries,which ,in turn,plays an important role in understanding and using great source of information.Additionally,it can be an instrument for learners to create future career path successfully.The ability to speak in English effectively opens door for everyone to reach goal in education ,business,tourism,medicine and etc.Let us highlight how we able to take advantage of English proficiency.